PENGARUH PEMODERASI PERTUMBUHAN LABA TERHADAP HUBUNGAN ANTARA UKURAN PERUSAHAAN, DEBT TO EQUITY RATIO DENGAN PROFITABILITAS PADA PERUSAHAAN PERDAGANGAN YANG TERDAFTAR DI PT. BURSA EFEK INDONESIA - Dini Afifah; Kamaliah -; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to know whether the company size and debt to equity ratio affects profitability moderated by earnings growth of trading company that listed in Indonesia Stock Exchange (IDX). The population in this study are all trading company registered in Indonesia Stock Exchange (IDX). Sampling was done using purposive sampling method, based on data collection there are 29 trading companies listed in Indonesia Stock Exchange. However, during the year 2009 there were delisted trading company namely PT. Tira Austenite Tbk and PT. Gema Grahasaran. Analysis of data using multiple regression method. The study states that the company size that moderated by earnings growth (X1) does not have a significant effect on the profitability. Debt to Equity Ratio moderated by earnings growth (X2) has a significant effect on the profitability of the company. Accoring to the rate coefficient of determination means that the profitability of the company is explained by the variable debt to equity ratio of firm size, debt-toequity ratio to earnings growth as moderating variables and the size of the companies with earnings growth as the moderating variable is equal to 36%. While approximately 64% is influenced by other variables that not examined in this study.Keywords: Firm Size, Debt to Equity Ratio, Profitability